1982
DOI: 10.1113/jphysiol.1982.sp014229
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical studies on the development of prochymosin‐ and pepsinogen‐containing cells in bovine abomasal mucosa.

Abstract: SUMMARY1. Prochymosin-and pepsinogen-containing cells in abomasal mucosa were simultaneously localized by means of an indirect immunofluorescence technique with specific rabbit antibodies.2. In the young milk-fed calves all the chief cells and several mucous neck cells produced both prochymosin and pepsinogen.3. By elution of the first antibody and retaining of the same section it was demonstrated that the same cells were producing both prochymosin and pepsinogen.4. In concentrate-fed calves and older cattle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…9). Fetal synthesis of pepsinogen A and progastricsin begins at about 140 and 180 days, respectively, and increases so that their summed level is nearly the same as that of prochymosin around weaning, 6~10 weeks after birth, before reaching a maximum in adult cattle [131].…”
Section: Change In Expression From Fetal/infant To Adult-type Pepsinomentioning
confidence: 99%
“…9). Fetal synthesis of pepsinogen A and progastricsin begins at about 140 and 180 days, respectively, and increases so that their summed level is nearly the same as that of prochymosin around weaning, 6~10 weeks after birth, before reaching a maximum in adult cattle [131].…”
Section: Change In Expression From Fetal/infant To Adult-type Pepsinomentioning
confidence: 99%
“…Samloff and Liebman (1973) and Liebman and Samloff (1978, 19791, on the other hand, found progastricsin (Pg 11) mainly in the chief and mucous neck cells of the fundic glands and in only the base of the pyloric glands in human, pig, cat, and dog. According to these investigators (Samloff, 1971;Samloff and Liebman, 1973), pepsinogen (Pg I) is produced in the fundic but not in the pyloric region of human, while we in this and earlier investigations (Andren et al, 1982;Andren and Bjorck, 1986) have shown the existence of pepsinogen immunoreactivity in most of the cells in both fundic and pyloric glands of cattle. This is most likely due to evolutionary differences, as the guinea pig (Cheret et al, 19741, cat, dog, andpig (Liebman andSamloff, 1978, 1979) also produce pepsinogen in both fundic and pyloric glands, while the rat has no pepsinogen (Pg I) at all in the stomach (Muto et al, 1980;Lai et al, 1988) and only produces progastricsin (Pg 11) in fundic and pyloric glands (Lai et al, 1988).…”
Section: Discussionmentioning
confidence: 77%
“…ready been reported by Andren et al (1982) and Andren and Bjorck (1986) and Miura et al (1988). Prochymosin-immunoreactive cells were found even in the primitive fundic gland of 10-week-old calf fetuses, and was then produced by almost all cells in the fundic gland as long as the calf was fed milk (shown to the age of 6 months).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The milk composition in the diet can stimulate the formation of mature chief cells excreting prochymosin and propepsin. Without stimulation of the milk composition, the fundus gland can only produce the chief cells secreting propepsin (Andren et al 1982). With continuous suckling, the secretion of prochymosin could last at least 6 months (Andren and Bjorck 1986).…”
Section: Discussionmentioning
confidence: 99%